Pengaruh Bahan Ajar Fisika Berbasis Model Problem Based Learning Menggunakan Pendekatan CTL Terhadap Berpikir Kritis Peserta Didik - Putri, Yosa Aulya; Yohandri, Yohandri (Jurnal Penelitian Pembelajaran Fisika, 2021)
The implementation of physics learning is still not optimal so that it affects the achievement of students' competencies. One of the reasons is the use of teaching materials that have not met the demands of the 2013 Curriculum. The teaching materials used still do not contain learning models and approaches, besides that, students' critical thinking skills are still categorized as low. The purpose of this study was to investigate the effect of using physics teaching materials based on a problem-based learning model using the CTL approach to improve students' critical thinking. This type of research was conducted by pretest-posttest control group design. Samples were taken using the purposive sampling technique. The research instrument consisted of a written test for knowledge competencies and a performance appraisal for skills competencies. The data analysis used includes descriptive statistical analysis, normality test analysis, homogeneity test, and hypothesis testing for the similarity of the two means. Based on the results of data analysis, it can be stated that the use of physics teaching materials based on the problem-based learning model using the CTL approach has a significant effect on the competence of knowledge and skills, as well as the critical thinking ability of students.